Application of automated corrosion sensors for monitoring the rate of corrosion during accelerated corrosion tests. Issue 5 (11th July 2012) - Prosek, T.; Le Bozec, N.; Thierry, D.
<x xml:space="preserve">Abstract</x> An automated corrosion monitoring system using the electrical resistance technique was applied for assessment of the corrosivity towards carbon steel and zinc in different phases of a complex accelerated corrosion test recently introduced by VDA, an association of German car makers. It comprises salt spray, wet, dry, and freezing phases. The developed small and battery‐driven atmospheric corrosion loggers provided high sensitivity allowing for sub‐angstrom (<10−10 m) measurements of corrosion depth and good accuracy. The actual corrosion rate was affected by the exposure history due to a limited rate of wetting/drying and oxygen and ion transport to the reaction interface under a layer of corrosion products. The hysteresis was particularly strong for carbon steel. Except the freezing phase, the steel corrosion rate varied in a narrow range from 0.2 to 0.6 µm/h. For zinc, the corrosion rate varied from 0.001 to 0.1 µm/h in particular phases of the cycle with the maximum in the salt spray phase. Seventy‐five percent of the metal corroded in the salt spray phase and in the following drying period representing only 13% of the total test time. The obtained data suggest that the proposed test cycle allowed for rather efficient drying of the zinc surface, which is believed to be crucial for the formation of corrosion products with certain protective ability observed also in field conditions.